Laser Versus Pneumatic Lithotripsy With Semi-Rigid Ureteroscope; A Comparative Randomized Study - Rabani, Seyed Mohammadreza; Rabani, Seyed Hossein; Rashidi, Najmeh (Journal of Lasers in Medical Sciences, 2019)
Introduction: Ureteral stones are among the most common disorders in the urologic field. Miniaturization of endoscopic devices in urology and extracorporeal shock wave lithotripsy (ESWL) has revolutionized the management of ureteral stones. The aim of this study was to compare the efficacy and results of laser versus pneumatic lithotripsy (PL) with semi-rigid ureteroscope in a randomized prospective clinical trial in removing stones. Methods: 117 adult patients underwent transurethral lithotripsy (TUL) in a single academic center and by a single surgeon. The patients were randomized in 2 groups: In group 1, 58 patients with ureteral stones underwent ureteroscopy and stone fragmentation was done by Ho: YAG laser lithotripsy (LL) and in group 2, 59 patients underwent PL (Swiss LithoClast) by using the same ureteroscope. Results: Mean age was 41.77 years and 41.1years in group one and 2 respectively (P = 0.79), there was no significant difference in male to female ratio and mean stone in both groups. The success rate for stone clearance was 79.31% and 77.96% in group 1 and 2 respectively (P = 0.52). No difference between complications was seen in both groups, but the duration of operations was different (significantly lower in group 2). Conclusion: In both techniques, acceptable results were achieved. We have found a significant statistical difference in duration of operation between our results (P = 0.001) and similar studies, while this was shorter in the pneumatic group in our study, it was longer in other similar ones. This might be a result of more experience in working with PL in our center. Keywords: Laser lithotripsy, Pneumatic lithotripsy, Ureteroscopy